The extent of the contribution of internal marketing in the management of human talent survey study of the views of some administrative leaders at the University of Mosul - حامد محمد محمود; حسن احمد حسين (Journal of Economics and Administrative Sciences, 2019)
Abstract Investment in the human resource has become an important part of the strategies of educational organizations so that they can be competitive, so that the access of academics in universities to the international awards as a result of their research excellence indicates the effectiveness of this human talent so the interest has emerged in the implementation of a strategy to manage these human talent in organizations in general and educational ones In particular as one of the power sources that can not be imitated. The focus of the organization on the interaction between the working people has increased attention to the human element in order to achieve the desired quality levels, which called for organizations that build this concept, which is known as internal marketing. This research attempts to urge the educational organizations to reconsider the plans and studies that they adopt in attracting human resources through the adoption of two concepts that are equally important (internal marketing, human talent management). The research was applied at the University of Mosul. A questionnaire was prepared specifically to measur the dimensions of the research on the Likert tripartite scale. Seventy questionnaires were distributed. The research community was represented by a sample of administrative leaders at the University of Mosul. A number of hypotheses were formulated which express the questions raised in the research problem,The Most important was (there is no relationship between internal Marketing and the human tolent management) The researchers used a set of statistical methods provided by the statistical package for social sciences (SPSS) to test the hypotheses formulated in the research. The researchers reached a set of conclusions that were highlighted by the results of the first hypothesis that there is a correlation between the internal marketing and the management of human talent, the researchers also made a set of recommendations, most important of which is the need to strengthen the interest of organizations in the practices and the management of human talent through the commitment to behaviors that support the nominally provide a supportive environment for staff talented and retain them in the organization by employing the concept of internal marketing.